1981
DOI: 10.1901/jaba.1981.14-261
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effects of Posted Feedback and Increased Police Surveillance on Highway Speeding

Abstract: A counterbalanced, reversal design was used to compare the effectiveness of posted feedback and increased police surveillance in reducing speeding on two urban highways. Drivers' speeds were measured using a concealed radar unit. During public posting, a large highway sign, which listed the percentage of drivers not speeding during the preceding week and the best record to date, was erected on each street. Use of the feedback sign alternated with periods of baseline and periods of increased police surveillance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
40
1

Year Published

1983
1983
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 4 publications
(10 reference statements)
4
40
1
Order By: Relevance
“…One technique that decreases vehicle speed is posting of the percentage of drivers not speeding, along with the best record to date, on a highway sign (Van Houten, Nau, & Marini, 1980;Van Houten & Nau, 1981). This technique reduced serious speeding (85th percentile speeding) by over 50%.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…One technique that decreases vehicle speed is posting of the percentage of drivers not speeding, along with the best record to date, on a highway sign (Van Houten, Nau, & Marini, 1980;Van Houten & Nau, 1981). This technique reduced serious speeding (85th percentile speeding) by over 50%.…”
mentioning
confidence: 99%
“…Moreover, the effects of the presence of the feedback sign in the original study have persisted for approximately 4 years at the time of this writing. Van Houten et al (1980) and Van Houten and Nau (1981) posted the percentage of drivers traveling less than 16 and 14 km/hr over the speed limit, respectively, as not speeding. These criteria for speeding were chosen rather than the posted limit because police authorities did not consider vehicles traveling under these speeds to be significant threats to safety.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This prospect has been an impetus for a program of research whose scope, nature, and purpose are suggested by terms such as community behavior analysis (Greene, 1981) and behavioral community psychology (Briscoe, Hoffman, & Bailey, 1975). This research has introduced behavioral engineering to systems responsible for energy conservation (Winett, 1980), traffic safety (Greene, Bailey, & Barber, 1981;Van Houten & Nau, 1981), and health care (Reiss, Piotrowski, & Bailey, 1976 Although community behavior analysis seems promising, it has generally introduced no more change in these systems than necessary to produce specific changes in the behavior of its consumers. For example, although consumers have been encouraged to comply with health care systems and to curtail consumption of fossil fuels, little complementary research has addressed the questionable practices of physicians and pharmaceutical companies (cf.…”
mentioning
confidence: 99%